Perpanjangan hasil Polymerase Chain Reaction (PCR) pada pasien Acquired Immunodeficiency Syndrome (AIDS): laporan kasus - Yoelius Wijaya Saputra; I Komang Parwata; Ni Komang Krisnawati (Intisari Sains Medis, 2022)
Background: Since its emergence in Wuhan in 2019, SARS-Cov-2 has become the virus that causes the ongoing pandemic situation. The number of infected humans continues to grow over time. Moreover, there is also the HIV virus which continues to be a global health problem. To date, the available data on the coinfection of SARS-Cov-2 with AIDS are limited. Case Presentation: This patient was found to have prolonged positive results on the Polymerase Chain Reaction (PCR) examination for 113 days. Female patient, aged 48 years, with complaints of shortness of breath since 3 days before admission to the hospital. Physical examination of the patient was compos mentis with a pulse rate of 113 beats per minute and a body temperature of 37.40C. On auscultation, crackles were found in both lung fields. The patient had anemia, leucocytosis, neutrophilia, lymphopenia, and elevated D-dimer. Conclusion: The destruction of CD4 and CD8 in AIDS patients can provide a protective effect against the inflammatory process and cytokine storm, but this milder symptom causes inadequate production of neutralizing antibodies. This low number of Neutralizing Antibodies causes prolonged PCR results in SARS-Cov-2 patients.   Latar Belakang: Sejak kemunculannya di Wuhan tahun 2019, SARS-Cov-2 telah menjadi virus yang menyebabkan situasi pandemik yang sedang berlangsung. Data manusia yang terinfeksi terus bertambah dengan sejalannya waktu. Disamping itu terdapat juga virus HIV yang terus menjadi masalah kesehatan global. Sampai saat ini, data yang tersedia tentang ko-infeksi penyakit SARS-Cov-2 dengan AIDS masih terbatas. Presentasi Kasus: Pada pasien ini ditemukan perpanjangan hasil positif pada pemeriksaan Polymerase Chain Reaction (PCR) selama 113 hari. Pasien perempuan, usia 48 tahun dengan keluhan sesak nafas sejak 3 hari sebelum masuk rumah sakit. Pemeriksaan fisik pasien compos mentis dengan laju nadi 113 kali permenit dan suhu tubuh 37,40 C. Pada auskultasi ditemukan ronchi di kedua lapang paru. Pasien mengalami anemia, leukositosis, neutrofilia, limfopenia, dan peningkatan D-dimer. Simpulan: Destruksi CD4 dan CD8 pada pasien AIDS dapat memberikan efek protektif terhadap proses inflamasi dan badai sitokin, akan tetapi gejala yang lebih ringan ini menyebabkan produksi Neutralizing Antibody yang terbentuk tidak adekuat. Jumlah Neutralizing Antibody yang kurang ini menyebabkan pemanjangan hasil PCR pada pasien SARS-Cov-2.